High interobserver variability of PTEN immunohistochemistry defining PTEN status in low- to intermediate-risk prostate cancer: results of the first German ring trial - Hommerding, Oliver; Bernhardt, Marit; Kreft, Tobias; Scherping, Anna; Abbas, Mahmoud; Baretton, Gustavo; Bräsen, Jan Hinrich; Breyer, Johannes; Darr, Christopher; Dressler, Franz Friedrich; Ellinger, Jörg; Erber, Ramona; et al. (Virchows Archiv, 2024)
The prognostication of individual disease trajectory and selection of optimal therapy in patients with localized, low-grade prostate cancer often presents significant difficulty. The phosphatase and tensin homolog on chromosome 10 (PTEN) has emerged as a potential novel biomarker in this clinical context, based on its demonstrated prognostic significance in multiple retrospective studies. Incorporation into standard clinical practice necessitates exceptional diagnostic accuracy, and PTEN’s binary readout—retention or loss—suggests its suitability as a biomarker. This multi-institutional ring trial aimed to validate the diagnostic precision of PTEN immunohistochemistry in localized, low- to intermediate-risk prostate cancer, across ten university pathology institutes in Germany. The trial incorporated 90 cases of patients diagnosed with acinar adenocarcinoma of the prostate of grade groups 1 (n = 8, 8.9%) and 2 (n = 82, 91.1%) post-radical prostatectomy. Remarkably, the interpretation of PTEN immunohistochemistry displayed substantial variation (12.5-51.2% PTEN loss rates) within an identical cohort of prostate cancer. Fluorescence in situ hybridization analysis demonstrated PTEN hemizygous deletions in 5.5% (5/90) of cases. All cases with hemizygous deletions presented a distinct loss of PTEN expression by immunohistochemistry and were unanimously identified as PTEN loss by all participants (sensitivity 100%). However, negative (loss) immunohistochemistry was relatively non-specific for an underlying genomic deletion. Improved inter-observer agreement was observed in a subsequent ring trial. Finally, we identify S473-pAKT immunohistochemistry as a useful marker in equivocal cases. In summary, this multi-institutional ring trial illustrates surprisingly heterogeneous outcomes in defining PTEN status by immunohistochemistry.
Online veröffentlicht: 9. Dezember 2024
Gesehen am 11.06.2025